Unrestricted access : new and classic short fiction - Rollins, James, 1961- (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"At the center of Unrestricted Access is the never-before-published novella "Sun Dogs. Other stories-each with an introduction by James Rollins-are just as compelling, offering broader insight into this acclaimed master's fictional universes, including: "The Pit": a young dog is kidnapped and brutalized into becoming the bloody champion of a dog-fighting ring. But can this tortured monster find redemption and a path back to the boy who first raised him with love and compassion? "Tagger": A pair of teenage street artists must protect San Francisco from a demon who has been seeking revenge for centuries. "The Devil's Bones": In this jungle adventure-the first joint story from Rollins and Steve Berry-Commander Gray Pierce and Cotton Malone must work together using their unique skills to survive a deadly threat. The stories "The Midnight Watch," "The Skeleton Key,"